Semi-transparent boundary in Lee–Wick electrodynamics - E. H. Rodrigues; F. A. Barone; F. E. Barone; L. H. C. Borges; A. A. Nogueira (European Physical Journal C: Particles and Fields)
Abstract In this paper, we investigate certain aspects of Lee–Wick electrodynamics near a semitransparent planar mirror. Specifically, we derive the modified propagator for the Lee–Wick gauge field in the presence of the mirror and conduct a detailed analysis of the interaction energy and the interaction force that arise between the mirror and a stationary point-like charge. We demonstrate that there are several peculiarities in this interaction compared to the results obtained for Maxwell electrodynamics. Our focus is on the divergences mitigated by the Podolsky mass term.